Accessory neurovascular foramina on the lingual surface of mandible: Incidence, topography, and clinical implications - B V Murlimanju; K G Prakash; D Samiullah; Latha V Prabhu; Mangala M Pai; Rjanigandha Vadgaonkar; Rajalakshmi Rai (Wolters Kluwer Medknow Publications, 2012)
Context: It was suggested that the accessory neurovascular foramina of the mandible might be of significance in relation to the effectiveness of local anesthesia following the routine inferior alveolar nerve block. Aims: To investigate the incidence of neurovascular foramina over the lingual surface of the mandible in South Indian population. Settings and Design: The study was conducted at the department of anatomy. Materials and Methods: The study included 67 human adult dry mandibles, the exact ages and sexes of which were not known. The location and number of neurovascular foramina were topographically analyzed. Statistical Analysis Used: Descriptive statistics. Results: The foramina were observed in 64 mandibles (95.5%) and were often multiple in most of the cases. They were located between the two medial incisors in 8 mandibles (1.9%), between the medial and lateral incisor in 34 mandibles (50.7%; 25-bilateral; 7-right; 2-left), between the lateral incisor and canine in 7 mandibles (10.4%; 2-bilateral; 3-right; 2-left), between the canine and first premolar in 6 cases (8.9%; 3 on each side). Foramina were also present around the genial tubercle in 56 mandibles (83.6%). Among them, 52 mandibles showed a single foramen just above the genial tubercle, 34 mandibles had foramina below the tubercles, 13 mandibles had foramina on the right side of genial tubercle and 17 were having on the left side. Conclusion: Since the anatomical details of these foramina are important to various fields of dentistry and oncology, the present investigation was undertaken. The clinical significance and implications are emphasized.